Analisis Hubungan Pendekatan Penegakan Undang-Undang Lalu Lintas Terhadap Kepatuhan Masyarakat - Zulfikar, Faiz Raudhin; Akbar, Muhamad Dafi; Putra Siagian, Imanuel Nelson; Darussalam, Rezky Fabyo; Ilham, Muhamad; Simamora, Mexi Christian; Fadhlullah, Muhammad Azhar Zakiy; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The success of Traffic Law Enforcement itself is determined by various factors that influence it, starting from the substance of regulations, activities in implementing law enforcement efforts, to the culture of law compliance in society. Law enforcement in the traffic sector is explicitly regulated in the provisions of Law No. 22 of 2009 (UU LLAJ), as well as implementing regulations related to motor vehicle inspection procedures/methods regulated in PP 80/2012. In these provisions, there are various kinds of provisions/substances that regulate all activities or activities of legal objects and subjects in the traffic sector, both as law enforcement officers and the public (road users). In this scientific article, research was carried out using normative juridical methods (Legal Research), which means that research is carried out by analyzing or approaching a phenomenon or problem from the perspective of legal norms. After conducting the analysis, the author found that there are various factors that determine public compliance with traffic laws, including how big the government's role is and what kind of approach must be taken in enforcing traffic laws, how much awareness the public has in obeying traffic regulations, The factors in question include internal factors from society itself based on awareness of the importance of law and external factors that encourage society to comply with existing laws.